Instantaneous wave-free ratio compared with fractional flow reserve in PCI: A cost-minimization analysis. (1st December 2021) - Berntorp, Karolina; Persson, Josefine; Koul, Sasha M.; Patel, Manesh R.; Christiansen, Evald H.; Gudmundsdottir, Ingibjörg; Yndigegn, Troels; Omerovic, Elmir; Erlinge, David; Fröbert, Ole; Götberg, Matthias
Abstract: Background: Coronary physiology is a routine diagnostic tool when assessing whether coronary revascularization is indicated. The iFR-SWEDEHEART trial demonstrated similar clinical outcomes when using instantaneous wave-free ratio (iFR) or fractional flow reserve (FFR) to guide revascularization. The objective of this analysis was to assess a cost-minimization analysis of iFR-guided compared with FFR-guided revascularization. Methods: In this cost-minimization analysis we used a decision-tree model from a healthcare perspective with a time-horizon of one year to estimate the cost difference between iFR and FFR in a Nordic setting and a United States (US) setting. Treatment pathways and health care utilizations were constructed from the iFR-SWEDEHEART trial. Unit cost for revascularization and myocardial infarction in the Nordic setting and US setting were derived from the Nordic diagnosis-related group versus Medicare cost data. Unit cost of intravenous adenosine administration and cost per stent placed were based on the average costs from the enrolled centers in the iFR-SWEDEHEART trial. Deterministic and probabilistic sensitivity analyses were carried out to test the robustness of the result. Results: The cost-minimization analysis demonstrated a cost saving per patient of $681 (95% CI: $641 - $723) in the Nordic setting and $1024 (95% CI: $934 - $1114) in the US setting, when using iFR-guided compared with FFR-guided revascularization. The results were not sensitive to changes in uncertain parameters or assumptions. Conclusions: IFR-guided revascularization is associated with significant savings in cost compared with FFR-guided revascularization. Highlights: Coronary physiology to guide revascularization improves clinical outcome. Instantaneous wave-free ratio and Fractional flow reserve provide similar clinical outcome. Revascularization guided by Instantaneous wave-free ratio is cost saving compared to Fractional flow reserve.